Alteration of Knee Kinematics After Anatomic Anterior Cruciate Ligament Reconstruction Is Dependent on Associated Meniscal Injury. Issue 5 (April 2018) - Akpinar, Berkcan; Thorhauer, Eric; Irrgang, James J.; Tashman, Scott; Fu, Freddie H.; Anderst, William J.
Background: Limited in vivo kinematic information exists on managing meniscal injury during anterior cruciate ligament reconstruction (ACLR). Hypothesis: Isolated anatomic ACLR restores knee kinematics, whereas ACLR in the presence of medial meniscal injury is associated with altered long-term knee kinematics. Study Design: Cohort study; Level of evidence, 3. Methods: From March 2011 to December 2012, 49 of 57 participants in a clinical trial underwent anatomic ACLR with successful kinematic testing at 24 months after ACLR. Twenty-five patients had associated meniscal tears: medial (n = 11), lateral (n = 9), or bilateral (n = 5). With a dynamic stereo radiography system with superimposed high-resolution computed tomography scans of patient knees, kinematics were measured during downhill running. The initial single-support phase of the gait cycle (0%-10%) was analyzed. Results: Anterior tibial translation (ATT) was the only kinematic outcome between patients' ACLR and contralateral knees that had significant interactions among meniscal groups ( P = .007). There was significant difference in ATT between patients with intact menisci and medial tears ( P = .036) and with medial tears and lateral tears ( P = .025). Patients with intact menisci had no difference in ATT, with a negligible effect size between the ACLR and contralateral knees (mean ± SEM: 13.1 ± 0.7 mm vs 12.6 ± 0.5 mm, P = .24, Cohen d = 0.15, n = 24), while patients with medial meniscal tears had an increase in ATT, with a medium effect size between the ACLR and contralateral knees (15.4 ± 1.0 mm vs 13.2 ± 1.0 mm, P = .024, Cohen d = 0.66, n = 11). Conclusion: Associated medial meniscal injury in the setting of ACLR leads to increased ATT at 24-month follow-up. Furthermore, isolated anatomic ACLR in the absence of meniscal injury demonstrated no significant difference from native knee kinematics at 24-month follow-up during rigorous "high demand" knee activity with the current sample size. Patients undergoing anatomic ACLR in the presence of medial meniscal injury remained at a higher likelihood of sustaining altered long-term knee kinematics.